ON A CLASS OF HYBRID SYSTEMS VIA A NOVEL APPROACH FOR REAL-CODED GENETIC ALGORITHM WITH HYBRID SELECTION - ARUMUGAM, M. SENTHIL; RAO, M. V. C. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
A real-coded genetic algorithm (RGA) approach with hybrid selection method to compute the optimal control and cost (fitness) of a single stage hybrid system is investigated. A typical numerical example is included to illustrate the efficacy of the proposed algorithm, which gives the better solution in comparison with forward algorithm. Several statistical tests are also carried out to prove the improved performance of the proposed algorithm. ANOVA test and t-test are also done to verify the betterment of the RGA with hybrid selection. From the experimental approach of the various proportion of the hybrid selection, the right proportions of the hybrid selection is identified and tested.